Rapid and Precise HPLC Analysis of Polymer Monomers in Bacillus sp. CYR1-Derived Polyhydroxyalkanoates Using Alkali Decomposition Pretreatment - Young-Cheol Chang (Chemical and Materials Sciences: Research Findings Vol. 1, 2025)
Background: Plastics are widely used worldwide due to their characteristics of being inexpensive, capable of mass production, lightweight, and highly durable. Although plastic, with its excellent properties, has become an essential part of daily life, it poses a significant threat because it does not decompose naturally in the environment and can persist for decades due to its stable physical properties. This has raised concerns about their impact on various ecosystems, including terrestrial and marine environments. Polyhydroxyalkanoates (PHA), produced by various bacteria and archaea, are biodegradable plastics with similar thermoplastic and elastic properties to conventional plastics. Aim: The aim of the study is to develop a simple PHA quantification method using high-performance liquid chromatography (HPLC) with alkaline hydrolysis pretreatment. Methods: Analysis was conducted using an HPLC (SHIMADZU, Kyoto, Japan) equipped with a UV-VIS detector (SHIMADZU, SPD-10AV) and a separation column (SHIMADZU, SCR model). The PHBV produced by Bacillus sp. CYR1 strain was quantified using both the developed method and GC analysis, and the quantification results were compared. A de-gassed peracetic acid solution (860 \(μ\)L/L) was used as the mobile phase at a flow rate of 1.5 mL/min. Results: By developing a simple PHA quantification method using alkaline hydrolysis pretreatment combined with HPLC, we attempted to quantify PHAs consisting of molecular chains longer than PHB by applying a simplified pretreatment process with HPLC. The retention times for standard reagents 2BE, 2PE, and 3HB were 11.1 minutes, 15.1 minutes, and 6.4 minutes, respectively. Additionally, the formation of 2BE and 2PE was observed from the PHA subjected to alkaline hydrolysis pretreatment, and the generated calibration curves demonstrated linearity. As P(3HB-co-3HV) is a copolymer of 3-hydroxybutyrate (3HB) and 3-hydroxyvalerate (3HV), 2BE and 2PE are produced by the alkaline decomposition of P(3HB-co-3HV). For this, we used the equation P(3HB) = \(α\) × 2BE and P(3HV) = \(β\) × 2PE, because the production ratio \(α\) of 2BE from P(3HB) and the production ratio \(β\) of 2PE from P(3HV) are constant in the reaction under the same decomposition conditions. The bacteria Chromobacterium violaceum and Bacillus sp. CYR1 were used to produce P(3HV) and P(3HB-co-3HV), respectively. The bacterium Bacillus sp. CYR1 produced 415 mg/L of P(3HB-co-3HV) when incubated with acetic acid and valeric acid as the carbon sources, whereas the bacterium C. violaceum produced 0.198 g of P(3HV)/g dry biomass when incubated with sodium valerate as the carbon source. Since there is no standard sample for P(3HV), it was produced in this study from C. violaceum. From the ratio of the slopes of the calibration curve, the production ratios were determined as \(α\) =3.26 and \(β\) =3.30. These results indicate that short-chain-length PHA (scl-PHA) can be quantified easily and with high sensitivity by measuring the 2BE and 2PE contents of actual samples using the method proposed here. Conclusion: It was confirmed that PHBV can be accurately quantified using the quantification method developed in this study. In the future, to assess the accuracy of the quantification results of PHBV in dried cell biomass, it will be necessary to validate the quantification method by performing GC analysis for comparison.